Cytoglobin scavenges intracellular hydrogen peroxide and regulates redox signals in the vasculature - Frances Jourd’heuil; Clinton Mathai; Le Gia Cat Pham; Kurrim Gilliard; Joseph Balnis; Katherine A. Overmyer; Joshua J. Coon; Ariel Jaitovich; Benoit Boivin; David Jourd’heuil (Redox Biology)
The oxidant hydrogen peroxide (H2O2) serves as a signaling molecule that alters many aspects of cardiovascular functions and contributes to cardiovascular diseases. Recent studies suggest that cytoglobin – a member of the globin family - may promote electron transfer reactions with proposed functions in H2O2 decomposition. In the present study, we directly examined the ability of cytoglobin to decompose H2O2. Carotid arteries from cytoglobin knockout mice were more sensitive to glycolytic inhibition by H2O2 than arteries from wild type mice. In addition, the ectopic expression of cytoglobin in cultured cells limited the inhibitory effect of H2O2 on glycolysis and reversed the oxidative inactivation of the glycolytic enzyme GAPDH. Cytoglobin facilitated the reduction of the thiol-based H2O2 sensor Hyper7 after H2O2 challenge. The specific substitution of one of two cysteine residues on cytoglobin (C83) inhibited its antioxidant activity, as did the substitutions at the proximal and distal histidine residues. In vitro, direct measurements of H2O2 concentrations indicated that purified cytoglobin consumes H2O2 at rates comparable to that of peroxiredoxin 2 and that it competitively inhibits the hyperoxidation of peroxiredoxin 2. We propose that cytoglobin may serve as a regulator of intracellular redox signals initiated by H2O2.